2005
DOI: 10.1007/s11211-005-8567-5
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Job Satisfaction: A Test of Three Competing Models

Abstract: Using nationally representative data, we test three theories about distributive and procedural justice and their relation to job satisfaction. Our results support the group-value model more than the personal outcomes model by showing that procedural justice is a more important predictor of job satisfaction than is distributive justice. Furthermore, although other research has supported the psychological contract model by showing that experiences with downsizing alter how procedural justice and distributive jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 47 publications
7
95
1
6
Order By: Relevance
“…In line with this finding, previous studies revealed that organizational justice has significant association with job performance (Bruker, 1996), trust to supervisors (Bace & Shapiro, 1897), organizational commitment (Qafuri, 2010, health of employees and reduction of work absences (Warner, 2005), customer satisfaction (ELvano, 2001), and managers' commitment (Teo et al, 2001). …”
Section: Discussionsupporting
confidence: 59%
“…In line with this finding, previous studies revealed that organizational justice has significant association with job performance (Bruker, 1996), trust to supervisors (Bace & Shapiro, 1897), organizational commitment (Qafuri, 2010, health of employees and reduction of work absences (Warner, 2005), customer satisfaction (ELvano, 2001), and managers' commitment (Teo et al, 2001). …”
Section: Discussionsupporting
confidence: 59%
“…Distributive justice may lead to job satisfaction as employees may expect a fair distribution of resources [79] and a fair chance at achieving their instrumental goals. On the other hand, procedural justice may also independently predict job satisfaction when individuals value fair procedures within the workplace [80] that convey respect of the organization towards individual employees [79]. This communication of respect confirms and guarantees employee importance in the organization, thus fulfilling their relational needs and improving their self-worth and eventually job satisfaction.…”
Section: The Mediating Role Of Distributive and Procedural Justice Inmentioning
confidence: 99%
“…In recent years, management researchers have shifted their attention to organizational justice, which considerably contributes to shaping employee attitudes and behaviors (Clay-Warner et al, 2005). Organizational justice is the fairness to employees in an organization (Randeree, 2008).…”
Section: Distributive Justicementioning
confidence: 99%